1980
DOI: 10.1111/j.1365-2621.1980.tb07571.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Various Treatments of Pulses on in Vitro Gas Production by Selected Intestinal Clostridia

Abstract: Studies were performed to find out the effect of different treatments of pulses, like cooking, fermentation, incorporation of spices like raw garlic, and ginger powder on in vitro gas production by selected intestinal Clostridia. All treatments had profound influence on gas production; the amount of gas was reduced between 30-60%. Maximum reduction was noticed at 1.0% concentration of spices. Lag phase of growth was prolonged considerably, suggestive of temporary suppression of gas production. C. perfringens p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1982
1982
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…Flatulence severity was significantly different among treatments during the EARLY (p < 0.0001) and LATE (p < 0.0001) phases and was ranked significantly higher with consumption of the chickpea and lentil treatments during the EARLY (p = 0.0004 and p = 0.0003, respectively) Waist/hip ratio Study Day 1 0.9 ± 0.1 0.9 ± 0.1 0.9 ± 0.1 0.9 ± 0.1 Study Day 29 0.9 ± 0.1 0.9 ± 0.1 0.9 ± 0.1 0.9 ± 0. and LATE (p < 0.0001 and p = 0.0001, respectively) phases when compared to the PRE phase (Table 4). These results suggest that flatulence production may depend on pulse type, an idea that is consistent with previous work comparing pulses for their in vitro gas (Garg et al, 1980) and in vivo flatus (Fleming, 1981) production. However, Table 4 shows that flatulence severity rankings were always very low (i.e.…”
Section: Flatulencesupporting
confidence: 85%
See 1 more Smart Citation
“…Flatulence severity was significantly different among treatments during the EARLY (p < 0.0001) and LATE (p < 0.0001) phases and was ranked significantly higher with consumption of the chickpea and lentil treatments during the EARLY (p = 0.0004 and p = 0.0003, respectively) Waist/hip ratio Study Day 1 0.9 ± 0.1 0.9 ± 0.1 0.9 ± 0.1 0.9 ± 0.1 Study Day 29 0.9 ± 0.1 0.9 ± 0.1 0.9 ± 0.1 0.9 ± 0. and LATE (p < 0.0001 and p = 0.0001, respectively) phases when compared to the PRE phase (Table 4). These results suggest that flatulence production may depend on pulse type, an idea that is consistent with previous work comparing pulses for their in vitro gas (Garg et al, 1980) and in vivo flatus (Fleming, 1981) production. However, Table 4 shows that flatulence severity rankings were always very low (i.e.…”
Section: Flatulencesupporting
confidence: 85%
“…In order to improve the acceptability of pulses and legumes, it has been common practice to remove the GOS (Garg, Banerjea, Verma, & Abraham, 1980;Ruperez, 1998) by overnight soaking followed by pressure cooking (discarding both soaking and cooking liquids), irradiation, germination, and enzyme treatments (Minorsky, 2003). These practices, once thought to improve the nutritional quality of pulses, must be reconsidered in light of the potential health benefits offered by GOS and pulses.…”
Section: Introductionmentioning
confidence: 99%
“…Silva and Braga (1982) also observed that cooking decreased the oligosaccharide content of a variety of beans (Phaseolus vulgaris L.) consumed in Brazil. Garg et al (1980) reported that cooking of chickpeas and peas caused a decrease in gas production in relation to that of uncooked seeds. In contrast, Rao and Belavady (1978) reported that cooking increased the oligosaccharide content of four different legume seeds consumed in India, and more recently, Reddy et al (1980) detected a slight increase in the stachyose and sucrose content of black gram (Phaseolus mungo L.) cotyledons and seeds after cooking.…”
mentioning
confidence: 99%